(untitled) (Stavební obzor - Civil Engineering Journal, 2021)
The multiple earthquakes have proved the effect of chained masonry walls on the seismic behavior of multistoried reinforced concrete buildings. The chained masonry walls have been considered one of the types of masonry infill walls but without gaps. This participation came intending to study this effect through the modeling of several two-dimensional frames for a multistoried reinforced concrete building, taking into account the hollow brick walls, which represent the most common type in Algeria. We analyzed the proposed models using ETABS finite element software, relying on the response spectrum method and respecting the most important requirements according to the applicable Algerian Seismic Code. After analysis of the different models, the results have been compared according to the parameters of the period, base shear, lateral displacement, and stiffness. Through a critical synthesis of the results, we concluded that these walls could significantly affect the seismic behavior of this type of buildings. Moreover, the neglect of these walls in the modeling process can lead designers to have a false perception of the behavior of these buildings towards seismic loadings.